3miles/ 28 minutes times 42 minutes is equal to 4.5 miles.
Therefore, Eric run 4.5 miles in 42 minutes.
Hopefully this helps!
i dunooo i dont even nooooo
I always make sure my hand brake is on
Answer:
![b=-6\\c=7](https://tex.z-dn.net/?f=b%3D-6%5C%5Cc%3D7)
Step-by-step explanation:
we know that
The general equation of a quadratic function in factored form is equal to
![y=a(x-x_1)(x-x_2)](https://tex.z-dn.net/?f=y%3Da%28x-x_1%29%28x-x_2%29)
where
a is a coefficient of the leading term
x_1 and x_2 are the roots
we have
![a=1\\x_1=3+\sqrt{2}\\x_2=3-\sqrt{2}](https://tex.z-dn.net/?f=a%3D1%5C%5Cx_1%3D3%2B%5Csqrt%7B2%7D%5C%5Cx_2%3D3-%5Csqrt%7B2%7D)
substitute
![y=(1)(x-(3+\sqrt{2}))(x-(3-\sqrt{2}))](https://tex.z-dn.net/?f=y%3D%281%29%28x-%283%2B%5Csqrt%7B2%7D%29%29%28x-%283-%5Csqrt%7B2%7D%29%29)
Applying the distributive property convert to expanded form
![y=x^2-x(3-\sqrt{2})-x(3+\sqrt{2})+(3+\sqrt{2})(3-\sqrt{2})](https://tex.z-dn.net/?f=y%3Dx%5E2-x%283-%5Csqrt%7B2%7D%29-x%283%2B%5Csqrt%7B2%7D%29%2B%283%2B%5Csqrt%7B2%7D%29%283-%5Csqrt%7B2%7D%29)
![y=x^2-(3x-x\sqrt{2})-(3x+x\sqrt{2})+(9-2)](https://tex.z-dn.net/?f=y%3Dx%5E2-%283x-x%5Csqrt%7B2%7D%29-%283x%2Bx%5Csqrt%7B2%7D%29%2B%289-2%29)
![y=x^2-3x+x\sqrt{2}-3x-x\sqrt{2}+7](https://tex.z-dn.net/?f=y%3Dx%5E2-3x%2Bx%5Csqrt%7B2%7D-3x-x%5Csqrt%7B2%7D%2B7)
![y=x^2-6x+7](https://tex.z-dn.net/?f=y%3Dx%5E2-6x%2B7)
therefore
![b=-6\\c=7](https://tex.z-dn.net/?f=b%3D-6%5C%5Cc%3D7)